The Clinical Evidence-Based Paradigm of Topical Anti-Aging Skincare Formulations Enriched with Bio-Active Peptide SA1-III (KP1) as Collagen Modulator: From Bench to Bedside [Corrigendum] - Rovero P; Malgapo DMH; Sparavigna A; Beilin G; Wong V; Lao MP (Clinical, Cosmetic and Investigational Dermatology, 2023)
Rovero P, Malgapo DMH, Sparavigna A, Beilin G, Wong V, Lao MP. Clin Cosmet Investig Dermatol. 2022;15:2693–2703. The authors have advised that there is an error in the Study characteristics for Face serum (ISPE, 2022) in Table 2 on page 2698. The correct Table 2 is as follows.